MTHFR polymorphism's influence on the clinical features and therapeutic effects in patients with migraine: An observational study - Guo, Jianhao; Hao, Xing; Wang, Rongrong; Lian, Ke; Jiang, Jun; Chen, Na; Feng, Zhiying; Rao, Yuefeng (Frontiers in Neurology, 2022)
Objective: The aim of our study was to evaluate individualized medicine based on methylenetetrahydrofolate reductase (MTHFR) polymorphism in patients with migraine. Methods: The data of 135 patients with migraine were collected from January 2021 to December 2021 in this study. MTHFR C677T genotypes were tested. The pain intensity was evaluated using numerical rating scale (NRS) during treatment. The folic acid, homocysteine (Hcy), vitamin B12, interleukin-2 (IL-2) and IL-4 levels, ferritin, and changes of NRS were compared among different genotypes of MTHFR in migraine patients. Results: The levels of Hcy and ferritin in male patients were higher than that in female patients (P < 0.05); Compared with CC and CT genotype group, TT genotype group showed significant increases in Hcy levels (P < 0.05) and decreases in folic acid levels (P < 0.05); When the folic acid treatment group was stratified by genotype, the TT genotype group showed a better therapeutic efficacy than conventional treatment group (P < 0.05) and reduce the severity of pain in migraine (P < 0.05). There’s no significant difference in therapeutic efficacy among other genotypes (P > 0.05). Conclusion: The detection of MTHFR gene provides a new basis for the treatment of migraine, and provides an individualized medication for migraine patients.